TNFSF15 inhibits VEGF‐stimulated vascular hyperpermeability by inducing VEGFR2 dephosphorylation. Issue 5 (9th February 2017) - Yang, Gui-Li; Zhao, Zilong; Qin, Ting-Ting; Wang, Dong; Chen, Lijuan; Xiang, Rong; Xi, Zhen; Jiang, Rongcai; Zhang, Zhi-Song; Zhang, Jianning; Li, Lu-Yuan
ABSTRACT: Vascular hyperpermeability is critical in ischemic diseases, including stroke and myocardial infarction, as well as in inflammation and cancer. It is well known that the VEGF–VEGFR2 signaling pathways are pivotal in promoting vascular permeability; however, counterbalancing mechanisms that restrict vascular permeability to maintain the integrity of blood vessels are not yet fully understood. We report that TNF superfamily member 15 (TNFSF15), a cytokine largely produced by vascular endothelial cells and a specific inhibitor of the proliferation of these same cells, can inhibit VEGF‐induced vascular permeability in vitro and in vivo, and that death receptor 3 (DR3), a cell surface receptor of TNFSF15, mediates TNFSF15‐induced dephosphorylation of VEGFR2. Src homology region 2 domain–containing phosphatase‐1 (SHP‐1) becomes associated with DR3 upon TNFSF15 interaction with the latter. In addition, a protein complex consisting of VEGFR2, DR3, and SHP‐1 is formed in response to the effects of TNFSF15 and VEGF on endothelial cells. It is plausible that this protein complex provides a structural basis for the molecular mechanism in which TNFSF15 induces the inhibition of VEGF‐stimulated vascular hyperpermeability.—Yang, G.‐L., Zhao, Z., Qin, T.‐T., Wang, D., Chen, L., Xiang, R., Xi, Z., Jiang, R., Zhang, Z.‐S., Zhang, J., Li. L.‐Y. TNFSF15 inhibits VEGF‐stimulated vascular hyperpermeability by inducing VEGFR2 dephosphorylation. FASEB J. 31, 2001–2012 (2017). www.fasebj.org